Enhancing Photovoltaic Thermal Management using a Water-Cooled System and Fresnel Lens Concentrator - Dewanto Harjunowibowo; Rini Iswandari; Nurcahya Pradana Taufik Prakisya; Teguh Pribadi Adinugroho; Dani Harmanto (Universitas Pendidikan Ganesha, 2025)
Photovoltaic (PV) solar cells continue to attract significant attention as a sustainable energy source due to their non-polluting nature, low operational costs, and minimal maintenance requirements. Despite these advantages, high operating temperatures remain a major factor that reduces PV efficiency and accelerates material degradation. PV cells exhibit optimal performance at specific temperature ranges under high solar irradiance; however, increased irradiance often leads to rapid temperature rise, potentially causing severe performance losses and material damage. This study aimed to investigate the effects of a water-cooled Fresnel lens (FL) concentrator on solar radiation absorption, heat dissipation, and overall PV efficiency. Water was circulated uniformly over the PV surface within an acrylic module, while a Fresnel lens was positioned above the module to focus incoming solar radiation. A water circulation capacity of 1 liter was employed and effectively insulated to minimize heat exchange with the surrounding environment, with a constant flow rate of 60 mL/min. Solar radiation of 420 Wh/m² generated by a halogen lamp beneath the Fresnel lens was used as the light source, and the experiment was conducted over a two-hour irradiation period. The results indicate that the Fresnel lens increased the incident solar power from the halogen lamp by approximately 20%. Moreover, the hybrid cooling–concentration technique reduced the front surface temperature of the PV panel by 14 °C and the rear surface temperature by 7 °C. However, the overall PV efficiency decreased by approximately 50%, primarily due to photon attenuation caused by the acrylic layer and the water flow. Despite this efficiency reduction, the hybrid system offers additional benefits, including extended PV lifespan and the potential utilization of the extracted excess heat for domestic applications.